Redescription of immature stages of central European fireflies, Part 3: Phosphaenus hemipterus (Goeze, 1777) larva, and notes on its life cycle and behaviour, with a key to three central European lampyrid larvae (Coleoptera: Lampyridae) - Novák, Martin (Zootaxa, 2018)
The mature larva of the elusive firefly Phosphaenus hemipterus (Goeze, 1777) is thoroughly redescribed and illustrated with detailed images, including scanning electron microscope figures. The external sense organs and their significance is discussed, as well as the predatory behaviour and specific lifestyle of the larva. A key to the central European lampyrid larvae (viz. P. hemipterus, Lamprohiza splendidula (Linnaeus, 1767) and Lampyris noctiluca (Linnaeus, 1758)) is provided as well as a comparative table of their morphological features.